بصیرتِ قرآن" للشیخ آصف قاسمی: منھج و خصائص": “Baṣīrat-e-Quran” by Āṣif Qāsmī: Methodology and Characteristics (Al-Qamar, 2018)
This article studies the methodology and characteristics of “Baṣīrat-e-Quran”, a Qur’ānic commentary written by Mawlānā Muhammad Āsif Qāsmī, founder of “Dārul ʻUloom Canada” and the great grandson of one of the founders of “Dārul ʻUloom Deoband” Mawlānā Qāsim Nānotavī. It finds that the referred tafsīr is among the significant commentaries of the Quran that address the contemporary issues in the light of Qur’ānic verses. Keeping in view the modern Western society, the tafsīr discusses modern social issues such as family planning, homosexuality, retribution, and racism etc. It also disproves the notions and concepts of Qādiānīs and Munkireen-e-Ḥadīth.
Keywords: Tafsīr; “Baṣīrat-e-Quran; Muhammad Āsif Qāsmī; Characteristics